Perspektif Politik Hukum Sehubungan Ketentuan Pembuktian Secara Sederhana Dalam Penyelesaian Utang-Piutang Menurut Hukum Kepailitan - Yofi Permatasari; Ariawan Gunadi (CV Rewang Rencang, 2024)
This study aims to determine the perspective of legal politics in relation to the provisions of simple proof in the settlement of debts in bankruptcy law. The research method used in this study is a literature study which is a study that focuses on the analysis of written materials based on their context. The written materials used in this study are in the form of manuscripts, articles, and journals. This study uses a descriptive research nature that prioritizes explanations regarding the object of research. The results obtained are that simple proof is a proof that focuses on examining bankruptcy petition cases. Where the petition for a statement of bankruptcy must be granted if there is a fact that the debtor has 2 or more creditors and has debts that are due and can be collected. In relation to legal politics, the amendment of Law Number 4 of 1998 to Law Number 37 of 2004 is difficult, because there are several obstacles in changing it.